Production of lipids by tetraselmis sp. Grown in palm oil mill effluent - Natanamurugaraj, Govindan; Pushparani, Chadayam; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim; Ahmad Ziad, Sulaiman; Yusuf, Chisti (AIP Publishing, 2022)
Malaysia is one of largest palm oil producer and exporter in the world, which generates million tons of palm oil mill effluent (POME) in a year. Discharge of POME into water bodies had created major environmental pollutions in Malaysia. Other side, POME also comprised of organic and inorganic pollutants that can become as potential medium source for cost-effective wastewater treatment and biofuel production. The fresh water microalgae Tetraselmis sp. was isolated from Taman Gelora, Kuantan, Pahang. The isolated pure strain of Tetrasemis sp. was cultivated in different concentration of palm oil mill effluent medium (5%, 10%, 15% and 20%, v/v). The results disclose that the maximal growth and biomass productivity was found in 10% (v/v) concentration of POME. The maximal dried biomass 0.832g/mL and extracted total lipid content 37% was obtained. The chemical characteristics of POME before and after cultivation were pH (7.9-8.1), BOD (38-11mg/L), COD (370-192mg/L), nitrate (247-10mg/L) and phosphate (22-0.7mg/L) respectively. Gas chromatography mass spectrometry depicts fatty acid methyl ester such as palmitic acid 55.03%, stearic acid 30.83 %, palmitoleic acid 7.67% oleic acid 4.84 %, linoleic acid 5.79% and followed by gamolenic acid 3.56 %. It proves that Tetraselmis sp. one potential candidate for biodiesel production by utilizing the palm oil mill effluent medium which can contribute to the reduction of the pollution.